Thin Layer Drying Kinetics of Dried Mango Acid at Different Drying Temperature in A Food Dehydrator - Rauf, Reski Febyanti; Sari, Dian Aninda; Syam, Husain; Jamaluddin, Jamaluddin; Rivai, Andi Alamsyah (Agricultural Technology Education Study Program, 2023)
Dried mango acid has been known for a long time as a traditional food product made from unripe mangoes. This product is dried to treat damaged mangoes due to an abundant harvest. One of the drying methods that can be used for this product is a food dehydrator, but information regarding the kinetics of drying manganese acid for drying is still lacking. This study aimed to analyze the effect of drying temperature using a food dehydrator on the drying kinetics characteristics of dried mango acid. Young mango slices were dried at three temperature levels of 40oC, 50oC and 60oC until the moisture content reached equilibrium. Weight, moisture content, drying rate, moisture ratio, and effective moisture diffusivity were analyzed. The results of the moisture ratio analysis were applied and evaluated in several mathematical models of thin layer drying and the curve fitting process was carried out through the application of nonlinear regression analysis. The results showed that the most suitable mathematical model to describe the drying characteristics of a thin layer of mango acid using a food dehydrator is the Page model. The value of effective moisture diffusivity drying mango acid at a temperature of 40oC was 1.826 x 10-10 m2/s, a temperature of 50oC was 3.651 x 10-10 m2/s and a temperature of 60oC was 4.564 x 10-10 m2/ s. The results of this research can be used as information to optimize the mango acid drying process.